2003
DOI: 10.1207/s15430154jce1801_13
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Older Korean Americans' Participation in Colorectal Cancer Screening

Abstract: The findings suggest a need for further research addressing barriers to cancer screening in Korean Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 21 publications
5
33
1
Order By: Relevance
“…[39][40][41][42] Among studies including Asians, similar barriers have been identified. 29,[43][44][45][46] Bastani et al 47 found that feeling ''violated,'' not knowing where to obtain screening, and difficulties in obtaining an appointment were additional barriers to CRC screening. Of note, several studies show that foreign birth and low acculturation (fewer years of residence in the US and limited English proficiency) are negatively associated with CRC screening.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42] Among studies including Asians, similar barriers have been identified. 29,[43][44][45][46] Bastani et al 47 found that feeling ''violated,'' not knowing where to obtain screening, and difficulties in obtaining an appointment were additional barriers to CRC screening. Of note, several studies show that foreign birth and low acculturation (fewer years of residence in the US and limited English proficiency) are negatively associated with CRC screening.…”
Section: Discussionmentioning
confidence: 99%
“…Those having a history of bloody stool were more likely to have had FOBT than their counterparts (Juon et al, 2003).…”
Section: Korean Americansmentioning
confidence: 94%
“…Korean Americans who reported having ever had FOBT was 18%, and 5-14% had FOBT in the past year, 11% having ever had sigmoidoscopy and 11% having within the past 5 years, and 8% having colonoscopy within the past 5 years (Maxwell et al, 2000;Juon et al, 2003;Jo et al, 2008). Those having a history of bloody stool were more likely to have had FOBT than their counterparts (Juon et al, 2003).…”
Section: Korean Americansmentioning
confidence: 98%
See 2 more Smart Citations